A study of South African revealed comparative advantage of exports within the BRICS. - Nobantu Madikizela; Dr Rosemary Sibanda; Dr Ankit Katrodia (African Journal of Hospitality, Tourism and Leisure, 2019)
There is much debate about the long-term benefit of South Africa’s membership to the BRICS partnership. Generally, there has been a perception that all the other BRICS partner countries are growing to the detriment of the South African economy. The focus of this article is to analyse the growth trend of an exclusive group of export goods that were identified to have a high revealed comparative advantage for South Africa within the BRICS bloc in 2012. These were identified to be potential growth area for South Africa within the BRICS trading bloc. This research aims to assess if there is a significant change in the performance of these exclusive exports since they were identified. A non-probability sample of 20 South African export product categories was drawn from the full population of 37 export categories that possess a revealed comparative advantage. Statistical analyses revealed that out of the twenty export categories identified to have a high revealed comparative advantage for South Africa in 2012; eight have grown while five have declined over the period under review. The value for tourism to South Africa and BRICS nations per se, is also unpacked to a limited extent since the study has bearing on it. There is clearly much scope to conduct further research to explore the countries that require deeper diplomatic engagement to create access to markets for South African exporters.